The Effect of Adiponectin Recombinant in Rattus Norvegicus with Polycystic Ovarium Syndrome Model on Anti-Müellerian Hormone Expression - Joseph Chandra Relmasira; Jimmy Yanur Annas; Widjiati (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Polycystic Ovary Syndrome (PCOS) is an important disease that causes various healthproblems in women. Ovulation - infertility disorders are found in 60-85% woman with PCOS. Anti-Muellerian Hormone (AMH), a protein from Transforming Growth-b Family, often increased in patientwith PCOS and associated with severity and poor prognosis for assisted reproductive outcome. Dietaryand lifestyle changes are the first-line therapies but consistent application of this method is difficult toattain for people with PCOS. Adiponectin, a product by adipose cells have a significant reduction inobese and women with PCOS. The purpose of this study was to see the differences in AMH expressionbetween mice with polycystic ovary model treated with adiponectin recombinant and mice withpolycystic ovary model treated with placebo and control.Method: This research is an experimental study with a Post Test Only Control Group design. Thesample of this study was 3 months female Rattus norvegicus Wistar strain weighing 110-120 g. Thesample size was 36, which were divided into three groups, K0 (control group of mice with polycysticovary model), K1 (group of mice with polycystic ovary model that received placebo injection), and K2(group of mice with polycystic ovary model that received 5 μg/ml injection of recombinant adiponectin).Polycystic ovary model made by injecting 10 mg/Kg body weight testosterone propionate for 14 days.The injection is carried out at the proestrous stage. The three groups of mice in a period of 3 weeks aftertreatment, were surgically removed according to the sampling procedure, then the ovaries were given acode and immunohistochemical staining was performed to see the AMH expression in the ovaries. Thedata were collected, then statistical analysis was carried out using SPSS software.